Real estate allocation decision of Malaysian real estate investment trusts - Abdul Jalil, Rohaya (2012)
Many studies on Malaysian REITs (Real Estate Investment Trust ) have shown the ability to provide diversification benefits in the investment portfolio. The strong support from the Malaysian government such as the relaxation of taxable income and other incentives are still inadequate to convince the institutional investors to include REITs in their investment portfolio. The unique characteristics of Malaysian REITs in term of asset allocation caused it difficult to be evaluated by the investors. A few factors such as type of property, location, size of firm and capital structure of REITs had been identified as real estate allocation decision (READ) to influence REITs performance. While Malaysian REITs’ performance are based on expected return (ER), beta coefficient (ß) and dividend payout (Div). Multiple regression analysis (MRA) is utilized to assess the significant level of influence of READ on performance. The study objective is achieved with mixed results. It showed that only Div had significant influence (R2 value: 64%), while ER and ß are insignificant (both R2 value less than 6%). This indicated that investors seek a long term goal in REITs investment and stable distribution than price appreciation. This study suggests an outline of READ for Malaysian REITs. The outline of READ then was assessed through the past performances of Malaysian REITs to rationalize the characteristic, strength and weakness of influencing variables